Cryptolepine, the Main Alkaloid of the Antimalarial Cryptolepis sanguinolenta (Lindl.) Schlechter, Induces Malformations in Zebrafish Embryos - Kwesi Boadu Mensah; Charles Benneh; Arnold Donkor Forkuo; Charles Ansah (Biochemistry Research International)
Background. Previous studies on cryptolepine, the antimalarial and cytotoxic alkaloid of Cryptolepis sanguinolenta, showed that it preferentially accumulates in rapidly proliferating cells and melanin-containing tissues. Subsequently, we demonstrated that cryptolepine was toxic to murine embryos in vivo but no signs of teratogenicity. in vivo developmental studies can be confounded by maternal effects. Here, we hypothesized that cryptolepine-induced embryo toxicity occurs at least partly through direct inhibition of embryogenesis rather than indirectly through the induction of maternal toxicity. Aim. To determine the effects of cryptolepine on developing zebrafish embryos ex vivo. Methods. Healthy synchronized zebrafish eggs were treated with cryptolepine (10−1 − 5 × 102 μM), benzyl penicillin (6 − 6 × 102 μM), or mercury chloride (3.7 × 10−1 − 3.7 × 101 nM) from 6 to 72 hours postfertilization. Developing embryos were assessed at 24, 48, 72, and 96 hours under microscope for lethality, hatching rate, and malformation. Results. LC50 for cryptolepine in the study was found to be 260 ± 0.174 μM. Cryptolepine induced dose- and time-dependent mortality from the 24 to 96 hours postfertilization. Lower cryptolepine concentration (<100 μM) caused mortality, approximately 15–18%, only after the 48 hours postfertilization. The most sensitive period of embryo lethality corresponded well with the pharyngula (24 to 48 hours) and hatching (48 to 72 hours) stages of embryonic development. Cryptolepine (10−1 − 5 × 102 μM) dose dependently inhibited the hatching rate. At doses above 500 μM, hatching was completely inhibited. Mercury chloride (3.7 × 10−1 − 3.7 × 101 nM), used as positive control, induced a consistent pattern of embryo lethality at all stages of development, whereas benzyl penicillin (6 − 6 × 102 μM), used as negative control, did not induce any significant embryo lethality. Morphological examination of (postfertilization day 5) of eleutheroembryos treated during embryonic development with cryptolepine showed decreased body length (growth inhibition), decreased eye diameter and bulginess, enlarged pericardia, and enlarged yolk sac and muscle malformations. Conclusion. Cryptolepine induces malformations, growth retardation, and mortalities in rapidly dividing zebrafish embryos ex vivo.